2009
DOI: 10.1097/jom.0b013e3181990d8e
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Guideline-Based Care for Workers with Mental Health Problems

Abstract: GBC could be cost-effective, as lower direct costs lead to equal treatment outcomes of workers with common mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 47 publications
1
48
0
3
Order By: Relevance
“…Although psychotherapeutic interventions are often provided to employees with CMD, the effect of these interventions on RTW are not well understood [6,16]. To give more insight into the benefits of combining cognitive-behavioural and work-focused techniques [8,17], we conducted an earlier study in which we compared the effectiveness of two CBTbased psychotherapeutic interventions: treatment as usual consisting of R-CBT and W-CBT [9].…”
Section: Cbt-based Interventions For Employees With Cmdmentioning
confidence: 99%
“…Although psychotherapeutic interventions are often provided to employees with CMD, the effect of these interventions on RTW are not well understood [6,16]. To give more insight into the benefits of combining cognitive-behavioural and work-focused techniques [8,17], we conducted an earlier study in which we compared the effectiveness of two CBTbased psychotherapeutic interventions: treatment as usual consisting of R-CBT and W-CBT [9].…”
Section: Cbt-based Interventions For Employees With Cmdmentioning
confidence: 99%
“…In some studies, all participants were working at baseline [28,29,34], while in others, all participants were on work disability leave [30] or sick leave [20][21][22]24]. Four studies included a mix of participants who were working, on sick leave, or unemployed [23,25,[31][32][33].…”
Section: Study Characteristics (See Appendix 5-electronic Supplementamentioning
confidence: 99%
“…Of the studies identified, four were conducted in The Netherlands [20][21][22][23][24], four in the USA [25][26][27][28][29] and one each in Canada, Finland, Denmark, and Japan [30][31][32][33][34]. Ten were randomised controlled trials (RCTs) [20][21][22][23][24][25][26][27][28][29][31][32][33] and two were non-randomised studies (NRSs) with a separate control group [30,34].…”
Section: Study Characteristics (See Appendix 5-electronic Supplementamentioning
confidence: 99%
See 2 more Smart Citations